Alessandro Rocco. Gabriel García Márquez and the Cinema. Tamesis, 2014. - Silvio Gaggi (Studies in 20th & 21st Century Literature, 2019)
Review of Alessandro Rocco. Gabriel García Márquez and the Cinema. Tamesis, 2014
Keywords: Gabriel Garcia Márquez; cinema